The Rotifer fauna of Guatemala and Belize: survey and biogeographical affinities - Estrella García Morales, Alma (2007)
Rotifer samples were obtained from 29 localities in northern Guatemala and central-southern Belize during March 2000 and June 2001. A total of 119 species were identified. Ten selected taxa are illustrated and commented: Euchlanis semicarinata, Lepadella apsicora, L. cryphaea, Lecane curvicornis f. lofuana, L. whitfordi, Monommata maculata, Scaridium bostjani, Trichocerca elongata f. braziliensis, and T. hollaerti. The species Lepadella rhomboidula is a first record for the American Continent. The species are 71 % cosmopolitan, 6 % tropicopolitan, and 4.2 % restricted to the subtropics. The Guatemala species number range was Petén-Itza lake (53 taxa), and Raxruja pool (three). La Democracia pool (49 taxa), and the Blue Hole sink-hole (six species) were the extremes in Belize. In total, 68 of the recorded taxa are new for Guatemala and 91 for Belize. Additionally, 47 species are registered by the first time in Central America. A comparison between these two countries and Mexico revealed that the south part of the latter conform a cluster with them, emphasizing the transitional character of this region between the Nearctics and the Neotropics. Furthermore, Guatemala and Belize have differences in species assemblages, as a response to the nature of their particular environments and topographical accidents.